Perancangan dan Implementasi Sistem Penjualan Berbasis Desktop Menggunakan Java NetBeans dan MySQL - Diana, Nirma Nur (Maliki Interdisciplinary Journal, 2025)
The development of information technology has encouraged various business sectors, including clothing stores, to switch to digital systems to support daily operational activities. To meet this need, a desktop-based clothing sales information system was developed specifically designed for store admins. This system is built using the Java programming language supported by NetBeans IDE and MySQL database as data storage media. This system applies object-oriented programming concepts such as class, object, and encapsulation during the development process. The main features provided include CRUD (Create, Read, Update, Delete) for managing product and transaction data, recording item codes, item names, customer names, prices, purchase quantities and calculating total amounts. In addition, this system is equipped with a Java-based Swing interface, which makes it easier for users to operate. The purpose of developing this system is to simplify the transaction process, reduce recording errors and improve service efficiency. Based on the implementation results, this system has been proven to help admins manage sales faster, more efficiently and more organized.